1994
DOI: 10.1177/088307389400900210
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in Infantile Autism

Abstract: Metabolic findings using [18F]fluorodeoxyglucose (FDG) with positron emission tomography (PET) and correlative anatomic findings with computed tomography (CT) or magnetic resonance imaging (MRI) were characterized in 13 children with infantile autism. Four of 13 patients had both an abnormal FDG-PET and an abnormal MRI, whereas seven of 13 patients had both a normal FDG-PET and a normal CT or MRI. Sixteen of a total of 195 brain areas qualitatively examined with FDG-PET had a hypometabolic abnormality on PET. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…Kemper and Bauman (1993) reported a coarse and poorly-laminated cingulate cortex in autism andother authors have presented functional evidence of abnormal connections, as well as a delay in the maturation of some cortical circuits [9][10][11][12] . Positron Emission Tomography (PET) and Magnetic Resonance Imaging (MRI) scans of autistic subjects suggest cortical ectopias, a distinctive feature of altered neuronal migration [10,[13][14][15] . The present study found no deviation from normal cortical layering pattern, evidence of ectopic cells, nor differences in the relative thickness of cortical layers in areas 22, 39 and 44 of brain from autistic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Kemper and Bauman (1993) reported a coarse and poorly-laminated cingulate cortex in autism andother authors have presented functional evidence of abnormal connections, as well as a delay in the maturation of some cortical circuits [9][10][11][12] . Positron Emission Tomography (PET) and Magnetic Resonance Imaging (MRI) scans of autistic subjects suggest cortical ectopias, a distinctive feature of altered neuronal migration [10,[13][14][15] . The present study found no deviation from normal cortical layering pattern, evidence of ectopic cells, nor differences in the relative thickness of cortical layers in areas 22, 39 and 44 of brain from autistic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…An uncontrolled, resting-state study of 13 autistic children (nine male, ages 4 -11 years) with comorbid mental retardation and seizure disorders qualitatively identified abnormalities, primarily hypometabolic foci, in five of the 13 children [Schifter et al, 1994]. The parietal, temporal, and occipital lobes were most frequently affected, followed by the thalami and cerebellum.…”
Section: Studies Of Brain Metabolism Using Positron Emission Tomographymentioning
confidence: 99%
“…Morphological investigations utilizing computed tomography (CT) and magnetic resonance imaging (MRI) have described several brain abnormalities without demonstrating any concordance in dysfunctions [6][7][8][9][10][11]. An interesting approach to detection comes from findings which suggest an anomalous hemispheric specialization [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%